2022
DOI: 10.1111/hel.12932
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance patterns of Helicobacter pylori in North Israel – A six‐year study

Abstract: Background: One main challenge in Helicobacter pylori (H. pylori) eradication is its increasing antibiotic resistance. Additionally, resistance rates vary between geographic areas and periods. However, data are limited since susceptibility testing is not routinely performed. Thus, it is valuable to gather data regarding H. pylori's resistance rates in Israel that would aid in better adjustment of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…3,12 Meta-analyses from the wider Asia-Pacific region have reported a substantial increase in levofloxacin resistance in recent decades, with the prevalence of levofloxacin-resistant H. pylori increasing from 7% before 2000 to 21% during 2011-2015. 13 Studies in the Middle East, 14 Italy, 15 Taiwan 16 and Southern Asia 17 have also demonstrated substantial increases in levofloxacin resistance within the past decade. The levels of levofloxacin resistance demonstrated in the current study exceed the limit of 15% recommended by the Maastricht VI/Florence Consensus Report for the use of empiric levofloxacin-based eradication therapy for refractory infection, since this antibiotic would be unlikely to achieve adequate (≥80%) eradication rates.…”
Section: Discussionmentioning
confidence: 99%
“…3,12 Meta-analyses from the wider Asia-Pacific region have reported a substantial increase in levofloxacin resistance in recent decades, with the prevalence of levofloxacin-resistant H. pylori increasing from 7% before 2000 to 21% during 2011-2015. 13 Studies in the Middle East, 14 Italy, 15 Taiwan 16 and Southern Asia 17 have also demonstrated substantial increases in levofloxacin resistance within the past decade. The levels of levofloxacin resistance demonstrated in the current study exceed the limit of 15% recommended by the Maastricht VI/Florence Consensus Report for the use of empiric levofloxacin-based eradication therapy for refractory infection, since this antibiotic would be unlikely to achieve adequate (≥80%) eradication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Clarithromycin and metronidazole resistance rates have been the highest-46.3% and 16.3%, resp. It is noteworthy that multi-resistance has been statistically higher in Arab in comparison to Jewish patients [18].…”
Section: Geographic Distribution Of Helicobacter Pylori Resistance To...mentioning
confidence: 90%
“…This study highlights the importance of continuous monitoring of H. pylori antibiotic resistance for increasing eradication rates of this bacterium. Therapy for H. pylori infection should be revisited and updated based on data on antibiotic resistance [62].…”
Section: Regional Characteristics Of H Pylori Resistancementioning
confidence: 99%